The 22 December 2018 tsunami from flank collapse of Anak Krakatau volcano during eruption - Ye, Lingling; Kanamori, Hiroo; Rivera, Luis; Lay, Thorne; Zhou, Yu; Sianipar, Dimas; Satake, Kenji (Science advances, 2020)
Rapid quantification of the Anak Krakatau landslide by regional seismic data could have aided in warning of the resulting tsunami. On 22 December 2018, a devastating tsunami struck Sunda Strait, Indonesia without warning, leaving 437 dead and thousands injured along the western Java and southern Sumatra coastlines. Synthetic aperture radar and broadband seismic observations demonstrate that a small, <~0.2 km 3 landslide on the southwestern flank of the actively erupting volcano Anak Krakatau generated the tsunami. The landslide did not produce strong short-period seismic waves; thus, precursory ground shaking did not provide a tsunami warning. The source of long-period ground motions during the landslide can be represented as a 12° upward-dipping single-force directed northeastward, with peak magnitude of ~6.1 × 10 11 N and quasi-sinusoidal time duration of ~70 s. Rapid quantification of a landslide source process by long-period seismic wave inversions for moment-tensor and single-force parameterizations using regional seismic data available within ~8 min can provide a basis for future fast tsunami warnings, as is also the case for tsunami earthquakes.